2016
DOI: 10.1038/ncomms12321
|View full text |Cite|
|
Sign up to set email alerts
|

Stromal Hedgehog signalling is downregulated in colon cancer and its restoration restrains tumour growth

Abstract: A role for Hedgehog (Hh) signalling in the development of colorectal cancer (CRC) has been proposed. In CRC and other solid tumours, Hh ligands are upregulated; however, a specific Hh antagonist provided no benefit in a clinical trial. Here we use Hh reporter mice to show that downstream Hh activity is unexpectedly diminished in a mouse model of colitis-associated colon cancer, and that downstream Hh signalling is restricted to the stroma. Functionally, stroma-specific Hh activation in mice markedly reduces th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 63 publications
7
104
2
3
Order By: Relevance
“…Additionally, we have demonstrated that stromal genetic or pharmacologic Hh pathway activation can reduce tumor burden in the AOM-DSS colon cancer model, as also recently reported elsewhere (30). Hence, the beneficial effects of Hh-mediated suppression of inflammation also extend to its downstream sequelae, namely progression to adenocarcinoma.…”
Section: Discussionmentioning
confidence: 49%
“…Additionally, we have demonstrated that stromal genetic or pharmacologic Hh pathway activation can reduce tumor burden in the AOM-DSS colon cancer model, as also recently reported elsewhere (30). Hence, the beneficial effects of Hh-mediated suppression of inflammation also extend to its downstream sequelae, namely progression to adenocarcinoma.…”
Section: Discussionmentioning
confidence: 49%
“…For bladder, we review evidence that niche-derived differentiation factors play an important role in restraining bladder cancer progression (Shin et al, 2014). Finally, we connect these studies to recent work demonstrating a surprisingly general cancer-restraining effect of stromal Hedgehog response in organs where the stem cells or their stromal niches are less well defined (Gerling et al, 2016; Lee et al, 2014; Rhim et al, 2014; Shin et al, 2014; Yang et al, 2016). …”
Section: Introductionmentioning
confidence: 55%
“…Potentially explaining the disappointing results of these clinical trials, recent work has shown a surprisingly general effect of stromal Hedgehog response in restraining cancer growth and progression, most notably in bladder (Shin et al, 2014), pancreatic (Lee et al, 2014; Rhim et al, 2014), colon (Gerling et al, 2016; Lee et al, 2016), and prostate (Yang et al, 2016) cancers. From these studies, several common themes emerge: (1) Hh signaling occurs in a paracrine fashion, with epithelial cells producing Hedgehog ligand and pathway activity exclusively restricted to stromal cells; and (2) Hedgehog pathway activation in stromal cells restrains growth and progression of primary epithelial tumors.…”
Section: Loss Of Stromal Niche Specification Facilitates Malignant Grmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, IHH gene knock-out leads to intestinal SC accumulation [57]. In addition, specific Hh activation in murine stromal cells induces complex transcriptional changes, leading to loss of colon SC-specific gene expression and upregulation of epithelial differentiation markers [58]. Most of the components of the Hh signaling pathway are upregulated (mRNA and protein) in CRC, with the exception of IHH that appears to be downregulated.…”
Section: The Hedgehog Pathwaymentioning
confidence: 99%